Enhanced waste cooking oil biodiesel with Al2O3 and MWCNT for CI engines. (1st February 2023) - Sathish, T.; Muthukumar, K.; Abdulwahab, AbdulKareem; Rajasimman, M.; Saravanan, R.; Balasankar, K.
Highlights: Produced Low-cost biodiesel from waste cooking oil and enhanced by Nanoparticles. Low-cost biodiesel enhanced with MWCNT and Al2O3 nanoparticles separately and collectively. Dual MWCNT and Al2O3 nanoparticles enhanced fuel outperformed by Higher BTE than diesel. MWCNT and Al2O3 combination minimized NOx emission, smoke, BSFC and ignition delay. BWCO/100 AONP recorded the lowest emission of CO and HC. Abstract: Fuel for diesel engines is highly demanded. Research on alternate fuel production is highly demanded to compensate for the steep raising demand rate. The low-cost fuel generation for them is the most important and indispensable research. This investigation aims to develop a low-cost and best alternate fuel from Waste Cooking oil and enhance its fuel properties with aluminium oxide nanoparticles (AONP) and Multi-Walled Carbon nanotubes (MWCNT). The biodiesel from the waste cooking oil was produced through the pyrolysis process with NaOH catalyst. Ultrasonicator is employed in preparing biodiesel and nano-fuel. The control group of fuels are Pure diesel (100 %) and B20 Biodiesel which was produced from waste cooking oil (BWCO). The experimental group of fuels includes nano-fuel of BWCO/100 MWCNT (BWCO + 100 ppm of MWCNT), nano-fuel of BWCO/100 AONP (BWCO + 100 ppm of AONP) and nano-fuel of BWCO/50 AONP/50 MWCNT (BWCO + 50 ppm of MWCNT + 50 ppm of AONP). For ensuring the fuel properties the prepared blends of B20 and nano-fuels, they were characterized in terms of density, kinematic viscosity, flashpoint, pour point, calorific value and cetane number. For ensuring the compatibility with the engine, both groups of fuels were tested common loads variation and observed Brake thermal efficiency, brake-specific fuel consumptions, In-Cylinder pressure, heat release rate. For ensuring the environmental hazardless measures, their exhaust gases were analyzed in terms of smoke opacity, hydrocarbon, Carbon monoxide and Nitrogen oxides emissions. It was found that nano-fuel of BWCO/50 AONP + 50 MWCNT recorded appreciable results like Brake thermal efficiency (BTE) of 30.65 %, In-cylinder pressure of 58.36 bar, heat release rate of 38.38 J/CAD with a minimum ignition delay of 9 CAD, NOx emission of 954 ppm, CO emission was 332 ppm and the smoke opacity were 31.2 % than pure diesel. These considerable differences in the nano-fuel than diesel in brake thermal efficiency are due to an increase of calorific values and Cetane number than the BWCO and diesel. Hence this investigation recommends a cheap and best alternate fuel for diesel engines.